2014
DOI: 10.3389/fpsyg.2014.00758
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in resting heart rate variability and cognitive control in posttraumatic stress disorder

Abstract: Post-traumatic stress disorder (PTSD) is characterized by deficits in cognitive functioning, particularly cognitive control. Moreover, these deficits are thought to play a critical role in the etiology and maintenance of core PTSD symptoms such as intrusive thoughts and memories. However, the psychophysiological concomitants of cognitive control remain largely unexamined. In this article, we suggest that individual differences in heart rate variability (HRV), a physiological index of self-regulatory capacity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 74 publications
(101 reference statements)
3
60
0
1
Order By: Relevance
“…Low HRV at rest is discussed as a risk factor for the development of anxiety disorders (Gillie & Thayer, ) since patients with anxiety disorders show similar deficits in safety learning and fear inhibition (Jovanovic, Kazama, Bachevalier, & Davis, ; Lissek et al, ) as well as reduced HRV at rest (Chalmers, Quintana, Abbott, & Kemp, ). Importantly, we have shown that low HRV may precede the development of self‐reported symptoms of anxiety (Gillie, Thayer, Vasey, & Heath, ).…”
Section: Discussionmentioning
confidence: 99%
“…Low HRV at rest is discussed as a risk factor for the development of anxiety disorders (Gillie & Thayer, ) since patients with anxiety disorders show similar deficits in safety learning and fear inhibition (Jovanovic, Kazama, Bachevalier, & Davis, ; Lissek et al, ) as well as reduced HRV at rest (Chalmers, Quintana, Abbott, & Kemp, ). Importantly, we have shown that low HRV may precede the development of self‐reported symptoms of anxiety (Gillie, Thayer, Vasey, & Heath, ).…”
Section: Discussionmentioning
confidence: 99%
“…A potential mechanism underlying the association between low HRV, anxiety, and exaggerated stress response may be related to impaired top-down prefrontal cortical modulation of autonomic activity (Gillie and Thayer, 2014; Thayer et al, 2009). It has been proposed that resting HRV may serve as a peripheral physiological index of self-regulatory capacity and integrity of CNS networks that support goal-directed behavior, in particular, the extent to which ‘top–down’ appraisals, mediated by cortical-subcortical pathways, can control brainstem activity and autonomic responses in the body (Park and Thayer, 2014; Thayer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, associations between RSA and both memory retrieval and cognitive control are observed during executive function tasks (Gillie, Vasey, & Thayer, 2014a, 2014b. RSA is also associated with PFC function as assessed via lesion studies (medial PFC; Buchanan et al, 2010), pharmacological blockade (both hemispheres; Ahern et al, 2001), functional magnetic resonance imaging (ventromedial PFC; see Thayer, Ahs, Fredrikson, Sollers, & Wager, 2012), retinal vessel analysis (Schuster, Jarczok, Fischer, Thayer, & Vossmerbaeumer, 2014), and cerebral blood flow assessed via arterial spin labeling (several regions; Allen, Jennings, Gianaros, Thayer, & Manuck, 2015).…”
Section: Emotion Dysregulation and Youth Psychopathologymentioning
confidence: 99%